1974
DOI: 10.1111/j.1151-2916.1974.tb10921.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High‐Coercivity BaFe12O19

Abstract: Particles of BaFe,,O,,, were prepared by chemical coprecipitation; their magnetic properties were studied. A coercive force of 6000 Oe, one of the highest reported for isotropic BaFe,,O,,, was obtained. X-ray and Moessbauer studies were conducted to examine the mechanism of formation. Superparamagnetic Lu-Fe,O,, was present during synthesis. Ferrites were sintered from these precipitated powders by both the usual method and a hot-press-forging method. The observed magnetic characteristics result from partial o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

1974
1974
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(64 citation statements)
references
References 10 publications
1
61
0
2
Order By: Relevance
“…In order to achieve a homogeneity of ions at the atomic level, and to overcome the effects of milling, various techniques such as chemical coprecipitation [107,108], glass crystallization [101,109], organometallic precursor method [110,111], aerosol synthesis [112,113], and colloidal synthesis [114] have been developed to prepare ultrafine barium ferrite. We have used the aqueous cores of water-in-oil microemulsions as reaction media to produce uniform-sized, microhomogeneous nanoparticles of carbonate precursors for the synthesis of ultrafine barium ferrite [92,931. We selected a microemulsion system with eetyl trimethyl ammonium bromide (CTAB) as the surfactant (12% by wt); n-butanol as the co-surfactant (10% by wt); n-octane (44% by wt) as the continuous oil phase; and a salt solution (34% by wt) as the dispersed aqueous phase.…”
Section: A Synthesis Of Barium Ferritementioning
confidence: 99%
“…In order to achieve a homogeneity of ions at the atomic level, and to overcome the effects of milling, various techniques such as chemical coprecipitation [107,108], glass crystallization [101,109], organometallic precursor method [110,111], aerosol synthesis [112,113], and colloidal synthesis [114] have been developed to prepare ultrafine barium ferrite. We have used the aqueous cores of water-in-oil microemulsions as reaction media to produce uniform-sized, microhomogeneous nanoparticles of carbonate precursors for the synthesis of ultrafine barium ferrite [92,931. We selected a microemulsion system with eetyl trimethyl ammonium bromide (CTAB) as the surfactant (12% by wt); n-butanol as the co-surfactant (10% by wt); n-octane (44% by wt) as the continuous oil phase; and a salt solution (34% by wt) as the dispersed aqueous phase.…”
Section: A Synthesis Of Barium Ferritementioning
confidence: 99%
“…En el mecanismo de reacción no se forman las fases intermedias MFe204, M2Fe205 ó MFe03_x (M = Ba, Sr) que se producen en el método cerámi-co tradicional. Según avanza la reacción, el coprecipitado cambia a la fase a-Fe203 a 650 °C y se convierte finalmente en MFei20i9 (M = Ba, Sr) a unos 800 °C (47).…”
Section: Métodos De Coprecipitacionunclassified
“…ε-Fe2O3 exhibits spontaneous magnetization at a Curie temperature (TC) of 500 K. Figure 2b presents magnetization versus external magnetic field curve at 300 K, which shows a huge Hc value of 20 kOe. Before this finding, the largest Hc value among metal oxide was 6 kOe of barium ferrite, BaFe12O19 [31], which indicates that the Hc of ε-Fe2O3 is over three times larger. The magnetic structure has been investigated using molecular field theory, which indicated that B and C sites have positive sublattice magnetizations, and A and D sites have negative sublattice magnetizations [32].…”
Section: Synthesis Crystal Structure and Magnetic Properties Of ε-Fmentioning
confidence: 99%